Strategi Implementasi Metode Activity Based Costing (ABC) dalam Menentukan Tarif Pelayanan Gigi di Klinik Abbasy Dental Purwokerto - Deni Hermansyah; Rian Andriani; Yen Efawati (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Pricing of healthcare services is a crucial element in clinic management, influencing operational sustainability and patient access to treatment. However, pricing practices in many dental clinics are still determined conventionally based on market rates without a systematic cost calculation. This study aims to analyze Implementation Strategy of the Activity Based Costing (ABC) method in determining dental service fees at Abbasy Dental Clinic Purwokerto. A Qualitative Methods approach was employed. Data were collected through in-depth interviews, direct observations, document analysis, and questionnaires administered to 50 patients and 10 clinic staff. The results indicate that the ABC method provides more accurate service cost calculations by identifying activities that generate expenses, including medical supplies (BHP), medical personnel fees, CSSD, dental equipment usage, dental unit costs, and administrative fees. The ABC-based pricing, using a 35% profit margin, resulted in final fees of IDR 226,125 for extraction, IDR 246,375 for GIC restoration, IDR 259,875 for scaling, and IDR 300,375 for composite restoration. Questionnaire results revealed positive patient perceptions regarding tariff transparency and fairness (mean > 4.18) and staff support for accuracy and efficiency in cost management (mean > 4.05). This study concludes that the ABC method can be applied as an accurate, fair pricing system that enhances patient trust and improves cost management effectiveness in dental clinics.